1998
DOI: 10.1038/34184
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-γ agonists inhibit production of monocyte inflammatory cytokines

Abstract: The peroxisome proliferator-activated receptor-gamma (PPAR-gamma) is a member of the nuclear receptor family of transcription factors, a large and diverse group of proteins that mediate ligand-dependent transcriptional activation and repression. Expression of PPAR-gamma is an early and pivotal event in the differentiation of adipocytes. Several agents that promote differentiation of fibroblast lines into adipocytes have been shown to be PPAR-gamma agonists, including several prostanoids, of which 15-deoxy-delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
1,913
8
48

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,321 publications
(2,035 citation statements)
references
References 26 publications
66
1,913
8
48
Order By: Relevance
“…Jiang et al 10 and Jiang et al 18 confirmed that PPARγ did express in human monocytes, and showed that PPARγ agonists (15d-PGJ2 and synthetic PPARγ ligands) could markedly upregulate PPARγ and processing of inflammatory cytokines in activated human macrophages at agonist concentrations similar to those found to be effective for the promotion of adipogenesis. Some genes are negatively regulated by PPARγ including inducible nitric oxide synthase, IL-1, IL-6, TNF-α, 10 and several other genes induced by interferon-γ (IFN-γ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Jiang et al 10 and Jiang et al 18 confirmed that PPARγ did express in human monocytes, and showed that PPARγ agonists (15d-PGJ2 and synthetic PPARγ ligands) could markedly upregulate PPARγ and processing of inflammatory cytokines in activated human macrophages at agonist concentrations similar to those found to be effective for the promotion of adipogenesis. Some genes are negatively regulated by PPARγ including inducible nitric oxide synthase, IL-1, IL-6, TNF-α, 10 and several other genes induced by interferon-γ (IFN-γ).…”
Section: Discussionmentioning
confidence: 88%
“…Human monocytes were isolated and prepared according to the protocol described by Jiang. 18 Experiments were conducted on the same day of blood collection, and all manipulations were carried out under endotoxin-free conditions. 18 …”
Section: Monocyte Preparationmentioning
confidence: 99%
“…Interest in PPARs increased dramatically when they were shown to be activated by medically relevant compounds including nonsteroidal antiinflammatory drugs [Lehmann et al, 1997]. Upregulation of PPARg reduces expression of several mediators of inflammation [Jiang et al, 1998] including MMP-1 in FLS stimulated with IL-1b [Fahmi et al, 2002a]. However, responses of cells to PPAR ligands can be due to activation of PPAR or can be PPAR independent [Fahmi et al, 2002b] actions which appear to be cell and stimulus, and perhaps ligand specific.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ activation reduces monocyte recruitment to atherosclerotic plaques 136. PPARγ also has a modulatory effect on inflammation and is known to decrease monocyte/macrophage production of several inflammatory cytokines 137. There is a large amount of evidence supporting the antiatherosclerotic properties of PPARγ, whether indirectly by improving control of lipid and blood glucose levels or directly by increasing plaque stability and direct actions on ECs, VSMCs, and macrophages 135.…”
Section: Implication Of Noncanonical Wnt Signaling In Vcmentioning
confidence: 99%